-2(6x-5)-5=-7

Simple and best practice solution for -2(6x-5)-5=-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(6x-5)-5=-7 equation:


-2(6x-5)-5=-7

We simplify the equation to the form, which is simple to understand
-2(6x-5)-5=-7

Reorder the terms in parentheses
+(-12x+10)-5=-7

Remove unnecessary parentheses
-12x+10-5=-7

We move all terms containing x to the left and all other terms to the right.
-12x=-7-10+5

We simplify left and right side of the equation.
-12x=-12

We divide both sides of the equation by -12 to get x.
x=1

See similar equations:

| 12x-9=32 | | xx=14 | | 4(y-1)=3(y+6) | | 12=m+5m | | 2+7x=42 | | 9=5n-5+2n | | 13y^2+2y-35=0 | | 4x-6x=2 | | 8(j+3)+24=16 | | y=2x^3 | | -10=-4-4a-2a | | 3(x+2)=9x-6 | | 3x=5x-2(x+3) | | -3=-5k+2k | | x^2-3x=37 | | -7=7+2u | | 2x-5=6x+9 | | 3(x-2)+x=6x-10 | | 7(x+2)=14 | | 6.1y-7=-7.9+5.8y | | 5y-8x=40 | | 5x-3(2x-8)=x | | 4s(3s+8)(7-5s)=0 | | (2t-3)(7t+1)=0 | | 20m-12m=16 | | 25x+2=12 | | w+j=p | | 4x+4x=29 | | 6j-4j-1=15 | | 10(v+6)-5v=20 | | 4-j=2 | | 3(f+3)=18 |

Equations solver categories